Pengembangan Media Papan Diagram Pada Materi Penyajian Data Peserta Didik Kelas IV SD - Adita, Asria; Misdalina, Misdalina; Irawan, David Budi (Scientia: Jurnal Hasil Penelitian, 2023)
This research is that the use of unvaried learning media makes the learning process boring, less interesting and less active for students. So, with this problem the authorities developed a media diagram board for learning mathematics on the data presentation material of the fourth grade of primary school. The research and development of this aim to produce a media board diagram for learning the mathematical on the presentation of data of the IV grade of elementary school that is valid, practical and effective. This research and development use a 4D development model that consists of 4 stages: 1) Definition, 2) Design, 3) Development, 4) Disseminate. The media validity of the diagram board was assessed by the media, material and language experts, the result obtained from the experts is an average of 91.1% with highly valid criteria based on the pick-up data. For the practicality gained from student responses at the one-to-one stage the pupil obtains an average score of 85.3% with highly practical categories, small group responses obtaining an average rating of 90.2% with very valid categories and for the effectiveness obtained from the test results the pupils obtain an average grade of 86.67% with very high categories.